SEARCHING FOR A NEW RATIONALE FOR COMPENSATING LOSS OF A CHANCE IN POLISH TORT LAW. LESSONS TO BE LEARNED FROM ENGLAND AND WALES - Sitnik, Piotr (Review of European and Comparative Law, 2017)
The question of compensation of loss of a chance is relatively rarely debated in the Polish doctrine of the law of tort. One reason for such a state of affairs may be the virtually unanimous opinion of both courts and academic comment-ators with regard to the permissibility of granting damages for loss of a chance of obtaining a benefit – loss of a chance, traditionally defined as potential harm, does not give rise to damages and falls beyond the scope of Article 361 § 2 of the Polish Civil Code. The paper attempts to show, by reference to the latest experiences of common law jurisdictions, that there exist rational bases for an extension of the notion of harm so that it encompasses loss of a chance where a potential acquisition of a benefit is contingent upon an action of a third party or force majeure, on which the victim has no bearing, subject to the caveat that the victim put an effort into generating the chance in question. In the course of the analysis an attempt will be made to demonstrate, with reference to a selec-tion of factual scenarios considered by Polish courts, that it would be possible to achieve fairer results (whilst avoiding placing unfair compensatory burdens upon the other party) to recognize liability for loss of a chance where the victim put a significant effort into making the chance viable, material, and where, based on ordinary life experience, materialization of such a chance may be considered a natural course of events.